The history of prostitution in Beitbridge 1950-1979 - Matimba, Itai (Midlands State University, 2017)
The research examines the history of prostitution in colonial Beitbridge from 1950 to 1979. It discusses the coming of women to Beitbridge and the origins of prostitution. The intensification of colonialism forced men into migrant labor. This exposed women to rural poverty since they were left alone taking care of themselves as well as the children. The colonial state preferred male labor and women were denied access to urban life. Women migrated to the town as traders and a few lucky ones were employed as domestic workers. However the success of African women entrepreneurs threatened the colonial state and laws were instituted to deny African women access to town as well as freedom to trade at the urban markets. With this, women were left with no choice except engaging in prostitution which led to the outbreak of venereal diseases. Archival sources, interviews, memos and secondary sources were used to come up with a convincing research.